Glycine Cleavage System H Protein Is Essential for Embryonic Viability, Implying Additional Function Beyond the Glycine Cleavage System - Leung, Kit-Yi; De Castro, Sandra C. P.; Galea, Gabriel L.; Copp, Andrew J.; Greene, Nicholas D. E. (Frontiers in Genetics, 2021)
Glycine cleavage system H protein (GCSH) is a component of the glycine cleavage system (GCS), a highly conserved protein complex that acts to decarboxylate glycine. Mutation of AMT or GLDC, encoding the GCS components aminomethyltransferase and glycine decarboxylase, can cause malformations of the developing CNS (neural tube defects (NTDs) and ventriculomegaly) as well as a post-natal life-limiting neurometabolic disorder, Non-Ketotic Hyperglycinemia. In contrast, it is unclear whether mutation of GCSH contributes to these conditions and we therefore investigated the effect of Gcsh loss of function in mice. Mice that were heterozygous for a Gcsh null allele were viable and fertile, and did not exhibit elevated plasma glycine. Moreover, heterozygous mutation of Gcsh did not increase the frequency of NTDs in Gldc mutant embryos. Homozygous Gcsh null mice were not recovered at post-natal stages. Analysis of litters at E8.5-10.5, revealed the presence of homozygous null embryos which were much smaller than littermates and had failed to develop beyond early post-implantation stages with no visible somites or head-folds. Hence, unlike null mutation of Gldc or Amt, which are compatible with embryonic survival despite the presence of NTDs, loss of function of Gcsh causes embryonic death prior to mid-gestation. Maternal supplementation with formate did not restore embryonic development beyond E7.5, suggesting that the primary cause of lethality was not loss of glycine cleavage activity or suppression of folate one-carbon metabolism. These findings suggest that Gcsh has additional roles beyond function in the glycine cleavage system, potentially acting in lipoylation of 2-oxoacid dehydrogenase proteins.